Interpretation of Metaphors and Similarities by Individuals With Cerebellar Lesions - Jodzio, Krzysztof (Przegląd Psychologiczny, 2024)
Objective: The cerebellum participates in both the coordination of motor activities and the regulation of mental processes. The symptoms of cerebellar damage are diverse, relatively non-specific, and difficult to systematize. Aim of the study: The aim of this exploratory study was to conduct a neuropsychological diagnosis of hypothetical disorders of selected (meta)linguistic and cognitive processes that are involved in solving problems containing metaphors and similarities. The epidemiology, severity, clinical specificity, and sociodemographic correlates of the analyzed disorders were characterized. Method: The study involved 25 adults with isolated cerebellar injury, most often of vascular origin. Three tests were used: the Polish version of the WAIS-R Similarities Subtest (PL) and two metaphor processing tests from the Polish version of the Right Hemisphere Language Battery (RHLB-PL), i.e. the Written Metaphor Test (TMP) and the Written Metaphor Explanation Test (TWMP). At the outset, the mean values and standard deviations were calculated for the whole group. In addition, each patient's test scores were assessed separately based on the data and norms included in the test manuals. Individual raw scores were replaced with converted scores and expressed in percentiles (similarities subtest) or on a sten scale (metaphor tests). Results: The performance on the WAIS Similarities Subtest was below average in the whole group, with 9 subjects having significant problems with solving the subtest. In turn, the score in the TWMP was determined in the range of 5–6 sten. Although the group’s overall performance in the TWMP did not differ from the norm, the result scored by nearly half of the subjects did not exceed 4 sten. In comparison, the average score on the TMP was relatively high, and low results (<4 sten) were obtained by only 4 patients. An estimated profile analysis (based on the pattern of all test results) showed intra- and inter-individual differences which were clinically illustrated by heterogeneous, often selective disorders of the examined functions. The sociodemographic correlates of test results were age and education. Conclusions: In the majority of patients, various cognitive deficits were implicated in disorders associated with solving problems that contain metaphors and similarities. Disorders in purposeful associative thinking, including inference by analogy and interpretation and verbalization of concepts, were predominant, whereas linguistic knowledge, including comprehension of figurative meanings, was generally unaffected.